Training tutors for implementing problem-based learning at a private medical college of Nepal - Joshi, Mili; Shrestha, Ira; Bhandary, Shital (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Problem based learning (PBL) is an innovative approach of teaching learning methodology in which, instead of traditional lectures, students are divided in small groups and provided with a problem which they try to solve. It has been used in different medical schools around the world for over 50 years. In Nepal, the use of PBL methodology is gradually increasing.Methods: Three experts on PBL content and process provided interactive lectures, hands-on exercises and plenary discussion sessions in 2014 at Lumbini Medical College. Effectiveness of the workshop was assessed by validated retro-prequestionnaire at the end of the workshop. Paired t-tests were used to test the differences between before and after scores on knowledge, application and opinion on PBL. Effect size was also calculated to determine the size of the difference between before and after the workshop.Results: The PBL training was effective as it increased knowledge, application and opinion on PBL of most of the participants. The workshop benefitted the most to the experienced male basic sciences faculty. However, clinical sciences faculty were skeptical of its application and their opinion on PBL did not change much whereas nursing faculty had some reservation on their opinion about PBL only.Conclusions: As PBL is implemented during the basic sciences years only, the concerned faculty benefitted the most from the workshop. Further such trainings are advocated to increase the pool of trained tutors for effective implementation of the PBL.Journal of Patan Academy of Health Sciences, Vol. 2, No. 2, 2015. page:7-12